Life Cycle of Pink Fungus (Upasia salmonicolor) in Java - Ambarwati-Harsojo Tjokrosoedarmo (Universitas Gadjah Mada, 1997)
In the complete life cycle of pink fungus, in this study five stages were recognized as follows: stage I (cobweb stage), stage II (pseudonodular stage), stage III (teleomorph), stage IV (nodular stage), and stage V (anamorph). The five stages are arranged into a sexual cycle (I, II, and III) on shady side of a branch, and asexual cycle (I, IV, and V) on exposed side of a branch. Most of the pink fungus on the 23 plant species found in this study formed only two or three stages of the sexual cycle. Only on apple, lime, calliandra, cinchona, coffee, oleander, crotalaria, and tephrosia, may the fungus form the complete five stages.